2022
DOI: 10.1186/s12940-022-00854-y
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study evaluating the risk of stroke associated with long-term exposure to ambient fine particulate matter in Taiwan

Abstract: Background Evidences have shown that the stroke risk associated with long-term exposure to particulate matter with an aerodynamic diameter of ≤2.5 μm (PM2.5) varies among people in North America, Europe and Asia, but studies in Asia rarely evaluated the association by stroke type. We examined whether long-term exposure to PM2.5 is associated with developing all strokes, ischemic stroke and hemorrhagic stroke. Methods The retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…33 Similarly, positive association between IS and measures of PM 2.5 and NO 2 by 2 cohort studies. 34,35 However, a cohort from the southeastern United States did not observe any association between PM 2.5 and IS. 36 In addition, a recent cohort study from the public health care system in Catalonia and Spain discovered that exposure to NO 2 but not PM 2.5 was associated with an increased risk of IS.…”
Section: Discussionmentioning
confidence: 88%
“…33 Similarly, positive association between IS and measures of PM 2.5 and NO 2 by 2 cohort studies. 34,35 However, a cohort from the southeastern United States did not observe any association between PM 2.5 and IS. 36 In addition, a recent cohort study from the public health care system in Catalonia and Spain discovered that exposure to NO 2 but not PM 2.5 was associated with an increased risk of IS.…”
Section: Discussionmentioning
confidence: 88%
“…For example, both the Danish Nurses cohort study and the Taiwan Chinese cohort study reported that chronic PM 2.5 exposure was related to an increased risk of ischemic stroke but not hemorrhagic stroke. 6,23 On the contrary, the Ontario Population Health and Environment Cohort from Canada demonstrated an increased risk of both stroke subtypes with higher PM 2.5 exposures. 24 The inconclusive findings may result from the misclassification of stroke subtypes, narrow range of PM 2.5 exposure levels, and relatively short follow-up durations.…”
Section: Discussionmentioning
confidence: 97%
“…However, existing evidence on the association of PM 2.5 with stroke subtypes is still insufficient and inconclusive. [4][5][6] Most of the studies supported a significant association between PM 2.5 and ischemic stroke, while the results for hemorrhagic stroke remain controversial. 4 Furthermore, compared with Western countries, Asian populations, including Chinese and Japanese, have a higher incidence of overall stroke and proportion of hemorrhagic stroke.…”
mentioning
confidence: 99%
“…Seven clusters of urbanization stratification were grouped into four levels: high, medium–high, medium, and low urbanization, according to the previously published consensus methodology 45 . Clusters of high bladder cancer incidence rate in the black-foot disease endemic regions included six southwestern coastal townships where people unknowingly drank arsenic-contaminated well water before tap water installation in 1979–2003 46 48 .…”
Section: Methodsmentioning
confidence: 99%